ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN KAP DI INDONESIA - Juwita Puspitasari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research is an empirical study to know the factors that influence the change of public accountant firm in Indonesia. Using factors such as management turnover, institusional ownership, share growth, audit opinion and client growth rate which is proxied by sales growth rate and assets growth rate. The population in this research are all the companies which are listed in “Bursa Efek Indonesia” (BEI) from 2010 until 2012. The selection of sample using purposive sampling method which obtain 72 companies as research sample, during three years and the total sample obtained are 216. The type of data is documentery data consist of published audited yearly financial statement. Analysis method using logistic regression. The result of logistic regression analysis shows that audit opinion and client growth rate which is proxied by assets growth rate have a significant effect to the change of public accountant firm. Though, the regression coefficient of audit opinion has the opposite direction with hypothesis. On the other hand, other variables like the management turnover, institusional ownership, share growth, and client growth rate which is proxied by sales growth rate do not have significant effect to the change of public accountant firm. Keyword: the change of public accountant firm, management turnover, institusional ownership, share growth, audit opinion and client growth rate.